Analisis Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Karyawan PT.Bintang Kadiri di Kediri - Putri Septi Naulina Hasibuan (Universitas Islam Kadiri, 2020)
The purpose in this research is to identify and analyze the influence of training and motivation as independent variables either partially or simultaneously on employee performance at PT.Bintang Kadiri as the dependent variable.In this research as the sample, used 50 employee of PT.Bintang Kadiri to fill questionnaire. The purpose is to determine the influence of training variable and motivation variable to employee performance used multiple linear regression statistical techniques and fatherly significance testing using the F test and t-test using SPSS 21. The result of this research : There is possitive and significant influence of training to the employee performance at PT.Bintang Kadiri, there is positive and significant influence of motivation to the employee performance at PT.Bintang Kadiri, there is significant and positive influence simultaneously of training and motivation to employee performance at PT.Bintang Kadiri.In this research can be concluded that the partial of the two independent variables ( training and motivation ) are significant influence to employee performance. The two independent variables ( training and motivation ) simultaneously have a significant influence to dependen variable ( employee performance ).